Does hydrotherapy help or hinder adaptation to training in competitive cyclists? - Halson, S. L.; Bartram, J.; West, N.; Stephens, J.; Argus, C. K.; Driller, M. W.; Sargent, C.; Lastella, M. (Medicine & Science in Sports & Exercise, 2014)
Purpose: Cold water immersion (CWI) may be beneficial for acute recovery from exercise, but it may impair long-term performance by attenuating the stimuli responsible for adaptation to training. We compared effects of CWI and passive rest on cycling performance during a simulated cycling grand tour.